Planning, politics, and public policy : the British, French, and Italian experience - Hayward, Jack Ernest Shalom; Watson, Michael (London ; New York : Cambridge University Press, 1975)
The book contains the British, French and Italian experience in planning, politics and public policy.
Includes index.
Bibliography: p. 484.
gp. 22/01/2019
Loans
Keywords: Great Britain; Great Britain; France; Italy